2020
DOI: 10.3390/plants9070905
|View full text |Cite
|
Sign up to set email alerts
|

Artifleck: The Study of Artifactual Responses to Light Flecks with Inappropriate Leaves

Abstract: Methods in sunfleck research commonly employ the use of experimental leaves which were constructed in homogeneous light. These experimental organs may behave unnaturally when they are challenged with fluctuating light. Photosynthetic responses to heterogeneous light and leaf macronutrient relations were determined for Cycas micronesica, Glycine max, and Zea mays leaves that were grown in homogeneous shade, heterogeneous shade, or full sun. The speed of priming where one light fleck increased the photosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“… Kromdijk et al (2016) have also shown that the bioengineered acceleration of the recovery from photo-inhibition increases the overall C uptake under fluctuating light in tobacco plants. On the contrary to our second working hypothesis, our experimental data support the idea that dynamic photosynthesis is not really detrimental in green varieties continuously grown under fluctuating light ( Vialet-Chabrand et al, 2017a ; Marler, 2020 ), either in LL or HL ( Figure 1B ), because of possible plants’ dynamic and developmental acclimations to ensure optimum resource use changes in their environment ( Gjindali et al, 2021 ). Li et al (2021) have also shown that photosynthetic different acclimation strategies in wheat can maximizes C assimilation under intermittent high light conditions, and this might also be the case for soybean.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“… Kromdijk et al (2016) have also shown that the bioengineered acceleration of the recovery from photo-inhibition increases the overall C uptake under fluctuating light in tobacco plants. On the contrary to our second working hypothesis, our experimental data support the idea that dynamic photosynthesis is not really detrimental in green varieties continuously grown under fluctuating light ( Vialet-Chabrand et al, 2017a ; Marler, 2020 ), either in LL or HL ( Figure 1B ), because of possible plants’ dynamic and developmental acclimations to ensure optimum resource use changes in their environment ( Gjindali et al, 2021 ). Li et al (2021) have also shown that photosynthetic different acclimation strategies in wheat can maximizes C assimilation under intermittent high light conditions, and this might also be the case for soybean.…”
Section: Discussioncontrasting
confidence: 82%
“…Contrarily to our initial hypothesis, dynamic photosynthesis seems to be detrimental to overall C uptake at canopy scale only for the chlorophyll deficient variety (MinnGold) in high light conditions, while the green variety (Eiko) seems to be well-adapted to light fluctuations in both low and high light. The fact that fluctuating light has been often reported to decrease C uptake in plants might be due to artifacts in the adopted protocols, which were not able to properly isolate the effects of dynamic light ( Marler, 2020 ). Our experiment did consider these last only and support the idea of new and more promising opportunities for the selection of greater crop photosynthetic efficiency by focusing on the variation in non-steady-state efficiency ( Acevedo-Siaca et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation